Institution versus Charism? The Emmanuel Community, the Catholic Church and John Paul II's World Youth Days. (9th September 2020) - Mercier, Charles
Abstract : This archive-based study aims to enlighten the way the Emmanuel Community, which is one of the most important Catholic charismatic international community, founded in France in 1973, participated in World Youth Days, the global mega gatherings of young Catholics initiated by Pope John Paul II in 1984. In doing so, it questions the complicated coexistence within Catholicism between geographical structures, including parishes, dioceses and national conferences of bishops, and transnational charismatic movements, which aggregate the faithful on the basis of spiritual affinities (and not according to the place they live in). It is argued that, despite initial failures and tensions, World Youth Days were an opportunity for the Emmanuel Community to be more included within traditional Catholic institutions, first in Rome and then in France.